The Impact of Social Security on Pension Claiming and Retirement: Active vs. Passive Decisions - Rafael Lalive; Arvind Magesan; Stefan Staubli (Institute of Labor Economics (IZA), 2020)
We exploit a unique Swiss reform to identify the importance of passivity, claiming social security benefits at the Full Retirement Age (FRA). Sharp discontinuities generated by the reform reveal that raising the FRA while imposing small early claiming penalties significantly delays pension claiming and retirement, but imposing large penalties and holding the FRA fixed does not. The nature of the reform allows us to identify that between 47 and 69% of individuals are passive, while imposing additional structure point identifies the fraction at 67%. An original survey of Swiss pensioners reveals that reference-dependent preferences is the main source of passivity.
Keywords: H55; J21; J26; 330; full retirement age; social security; regression discontinuity design; reference dependence